The application of social learning theory in predicting the antecedents of social entrepreneurial intention - Sijabat, Rosdiana (Business: Theory and Practice, 2024)
This study analyzes the influence of self-efficacy, role models, and attitudes toward social entrepreneurship on social entrepreneurial intention. It also examines the moderating role of role models in the relationship between self-efficacy and social entrepreneurial intention. This study uses a structural equation model to test five hypotheses. It relies on primary data collected through questionnaires distributed to 114 students from various Indonesian universities. These respondents, identified through convenience sampling, had all learned social entrepreneurship at their university. This study found that self-efficacy positively affects social entrepreneurial intention; role models also positively influence social entrepreneurial intention and attitude toward social entrepreneurship; and attitude toward social entrepreneurship positively impacts social entrepreneurial intention. Role models do not moderate the relationship between self-efficacy and social entrepreneurial intention. The originality of this research lies in its novel adaptation of social learning theory and social cognitive career theory to understand social entrepreneurial intention. As such, this study adds to the theoretical understanding of social entrepreneurial intention, which has been intensively studied using the theory of planned behavior.